The Relationship Between HBA1C Levels and Diabetic Complications in Patients with Type II Diabetes Mellitus at RSU Royal Prima Medan - Dalimunthe, Anita Rosari; Wijaya, Livinda Christy; Nasution, Sri Wahyuni (Newinera Publisher, 2023)
North Sumatra is home to a considerable population of Diabetes Mellitus (DM) patients, specifically individuals aged 15 years and above, totaling 49,572. Among the cities in the province, Medan stands out with the highest prevalence of Type II DM patients. The data indicates that in 2018 alone, the number of DM patients in Medan reached 7,826, solidifying its status as the primary contributor to the overall prevalence of DM in North Sumatra. The focal point of this research is to assess the understanding of the connection between HbA1c levels and complications in Type II Diabetes Mellitus patients, particularly those receiving care at Royal Prima Hospital in Medan. Employing a cross-sectional research design, the study involved 85 participants selected through purposive sampling, and data analysis was conducted using SPSS software. The study's outcomes highlight a significant relationship between HbA1c levels and complications in Type II Diabetes Mellitus patients at Royal Prima Hospital in Medan. This association is substantiated by the chi-square test results, yielding a p-value of 0.000, which is less than the significance threshold of 0.05. This statistical significance implies a robust and noteworthy correlation between HbA1c levels and the occurrence of complications in patients with Type II Diabetes Mellitus at the mentioned hospital.